Modeling and control of HIV infection - Du, Su Guo (2011)
Since the early eighties, tremendous effort has been made in modelling the human immunodeficiency virus (HIV) infection. HIV is the virus that causes AIDS (Acquired Immune Deficiency Syndrome). A number of mathematical models have been developed to describe the interaction of human immune system with the HIV. Before we present our HIV infection model, we give an introduction of Immunology and HIV infection in Chapter 1. Some other models related to HIV infection are also introduced.